Dynamical Analysis of Approximate Solutions of HIV-1 Model with an Arbitrary Order - Asma; Nigar Ali; Gul Zaman; Anwar Zeb; Vedat Suat Erturk; Il Hyo Jung (Complexity)
This article studies the dynamical behavior of the analytical solutions of the system of fraction order model of HIV-1 infection. For this purpose, first, the proposed integer order model is converted into fractional order model. Then, Laplace-Adomian decomposition method (L-ADM) is applied to solve this fractional order HIV model. Moreover, the convergence of this method is also discussed. It can be observed from the numerical solution that (L-ADM) is very simple and accurate to solve fraction order HIV model.